Case Report of Cryptococcus Albidus Peritonitis in a Peritoneal Dialysis Patient and a Review of the Literature. Issue 4 (July 2015) - Ragupathi, Loheetha; Reyna, Maria
Cryptococcus albidus is a saprophytic yeast linked to just 26 reports of human infection in the world literature. Here, we report the first case of C. albidus peritonitis, in a patient with end-stage renal disease and hepatitis C-associated cirrhosis who is on peritoneal dialysis. The patient was treated successfully with a week-long course of amphotericin B. Non-neoformans cryptococcal infections present a clinical challenge, because they are difficult to diagnose and lack established guidelines for treatment. We present a review of the literature on C. albidus infections and their treatment.